Gaps in immunization coverage at school entry and after two years of school attendance among immigrant and refugee children in Ontario, Canada - Sarah E. Wilson; Catharine Chambers; Andrew S. Wilton; Li Bai; Natasha Crowcroft; Shelley L. Deeks; Scott A. Halperin; Jeffrey C. Kwong; Meb Rashid; Karen Tu; Kumanan Wilson; Astrid Guttmann (PLoS ONE, 2025)
Background Foreign-born children may face greater barriers to accessing routine immunizations in Canada or their country of birth, but provincial surveillance data on immigration status are lacking. Using our provincial immunization repository linked to administrative data, we assessed immunization coverage among immigrant and refugee children in Ontario, Canada, compared with Ontario-born children and identified factors associated with being up-to-date (UTD). Methods We conducted a retrospective cohort study of children entering school during the 2012/13–2014/15 school years. We calculated UTD coverage for measles (2 doses), diphtheria (4 doses), and polio (3 doses) vaccines at school entry and two years after school attendance. We compared UTD coverage between immigrant/refugee children and Ontario-born children using standardized differences (SD). Results In a cohort of 363,662 children, 15,114 (4.2%) were immigrants/refugees (82.1% immigrants, 17.9% refugees). UTD coverage for all antigens combined was 59.2% among immigrant/refugee children compared with 87.9% among Ontario-born children at school entry (SD = 0.69), increasing to 84.9% and 94.3%, respectively, two years after school entry (SD = 0.31). Coverage was lower with greater disparities between immigrant/refugee and Ontario-born children for measles (87.9% vs. 94.8%, SD = 0.25) and diphtheria (94.6% vs. 97.4%, SD = 0.15) after two years than polio (97.1% vs. 98.4%, SD = 0.09). Among immigrant/refugee children, coverage was lowest in refugees (vs. immigrants), recent immigrants, and those born in certain regions. Conclusions Immunization coverage among foreign-born children lagged behind their Ontario-born peers, even after two years of school attendance. Findings varied by vaccine, immigration category, time spent in Ontario, and country of birth.